PENGARUH GAYA KEPEMIMPINAN TERHADAP BUDAYA ORGANISASI DI POLITEKNIK LP3I JAKARTA KAMPUS JAKARTA UTARA - Iis Kartini; Agung Edi Rustanto (JURNAL LENTERA BISNIS, 2018)
ABSTRACT This study entitled "The Effect of Leadership Style of Organizational Culture  In LP3I Polytechnic Campus Jakarta North Jakarta". The purpose of this study was to determine the influence of leadership style on organizational culture at Polytechnic LP3I Jakarta, North Jakarta Campus and determined the dominant leadership style indicators affect the organizational Culture at Polytechnic LP3I North Jakarta Campus conducted in this experiment, namely descriptive quantitative research methodsThe population of this research is all employees of Polytechnic LP3I North Jakarta Campus that counted of 33 empolyees and sampling technique used is by simple random sampling which resulted in a sample of 33 employees.The instrument used in this study was a questionnaire and analysis of the data used is simple regression. The results of this research that there is a positive and significant effect of leadership style on organizational culture amounted to 3.50%. There is a positive correlation between leadership style to organizational culture. Keywords: Leadership, Culture, Organization, Employees